(untitled) (Jurnal Manajemen dan Organisasi, 2019)
The Principle of profit-sharing operation in Sharia bank is often utilized for financing. However, in its practice, the distribution of Sharia Bank funds be done at the equivalent cost. This might occur due to the agency predicament in which Sharia Commercial Bank become a liaison between the depositor and the debtor who bring money. By conducting panel analysis of regression data at 11 sharia commercial banks in Indonesia during period 2012.Q1-2016.Q4, it was found that financial problems happen chiefly because of adverse Sharia Banks and moral hazard which intentionally increase financing.